Peran Promosi melalui Instagram, Kualitas Layanan dan Fasilitas Wisata terhadap Minat Berkunjung Kembali Wisatawan - Dianafakroh, Dianafakroh; Santi, Ira Nuriya; Syarifuddin, Umar; Evrianti, Hesti (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The study aims to determine the role of promotion through Instagram, service quality, and tourist facilities on tourists' intention to revisit Pantai Kura-Kura tourist location. The population of this quantitative study is not precisely known, so the sample was determined based on the criteria of followers of the Pantai Kura-Kura account and having visited the location. 120 respondents were then selected as a sample using non-probability sampling with a purposive sampling technique. The results of partial multiple linear regression analysis indicate that promotion through Instagram has no effect on tourists' intention to revisit Pantai Kura-Kura, while service quality and tourist facilities are proven to have a significant influence on this intention. Simultaneously, promotion through Instagram, service quality, and tourist facilities are proven to have a significant influence on tourists' intention to revisit.